New approach on confined particle bed breakage as applied to multicomponent ore. (January 2016) - Liu, L.X.; Powell, M.
Highlights: Linear relationship between product size ( t 10 ) and particle bed porosity reduction. No unique relationship between specific energy and size reduction in bed breakage. Mixture breakage product size can be predicted from that of single components. Mixture specific energy consumption can be predicted from that of single components. Abstract: The breakage characteristics of a two-component ore in a confined bed was studied in this work in order to predict the breakage behaviour of a multi-component ore from the properties of individual components. Bed compression tests with each single component and blended components at different bulk volumetric ratios were carried out at different volume based specific energies and the bed particle size distributions of each component in the mixtures were measured (through magnetic separation). The experimental results show that the breakage product size measured by t 10 – the cumulative mass percentage of particles less than 1/10th of the feed size, is linearly proportional to the relative bed porosity reduction, for both single component and multi-component ore. There is a minimum bed porosity reduction to be reached before any breakage occurs and the less competent the ore, the lower the minimum porosity reduction value. Theoretical analysis on bed compression breakage shows that the relationship between product size measured in t 10 and the specific comminution energy ( Ecs ) is not unique and is dependent on the testing conditions. The analysis shows the importance of testing bed breakage at conditions that are independent of bed configurations. Furthermore, models for predicting the product t 10 and specific comminution energy of multi-component ore from single component compression data are developed. By compressing the particle bed at the set porosity reduction for each component and few multi-component tests, one can predict the mixture product and mixture energy consumption at any mixture ratios without the needs to physically separate the products in the mixture test.